Energy Transfer and Cross-Relaxation Induced Efficient 2.78 μm Emission in Er3+/Tm3+: PbF2 mid-Infrared Laser Crystal - Jiayu Liao; Qiudi Chen; Xiaochen Niu; Peixiong Zhang; Huiyu Tan; Fengkai Ma; Zhen Li; Siqi Zhu; Yin Hang; Qiguo Yang; Zhenqiang Chen (Crystals, 2021)
An efficient enhancement of 2.78 μm emission from the transition of Er3+: 4I11/2 → 4I13/2 by Tm3+ introduction in the Er/Tm: PbF2 crystal was grown by the Bridgman technique for the first time. The spectroscopic properties, energy transfer mechanism, and first-principles calculations of as-grown crystals were investigated in detail. The co-doped Tm3+ ion can offer an appropriate sensitization and deactivation effect for Er3+ ion at the same time in PbF2 crystal under the pump of conventional 800 nm laser diodes (LDs). With the introduction of Tm3+ ion into the Er3+: PbF2 crystal, the Er/Tm: PbF2 crystal exhibited an enhancing 2.78 μm mid-infrared (MIR) emission. Furthermore, the cyclic energy transfer mechanism that contains several energy transfer processes and cross-relaxation processes was proposed, which would well achieve the population inversion between the Er3+: 4I11/2 and Er3+: 4I13/2 levels. First-principles calculations were performed to find that good performance originates from the uniform distribution of Er3+ and Tm3+ ions in PbF2 crystal. This work will provide an avenue to design MIR laser materials with good performance.